Odpowiedzi

2010-03-30T17:50:15+02:00
3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
-3x+2x+2x=8+2-9
x=1

4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
4x-3x-2x=4-4+6-5
-x=1/:(-1)
x=-1

4-5(3-x)=-x-(3-2x)
4-15+5x=-x-3+2x
5x+x-2x=-3-4+15
4x=8/:4
x=2

x-(7+2x)=2(x-1)+1
x-7-2x=2x-2+1
x-2x-2x=-2+1+7
-3x=6/:(-3)
x=-2

Myślę, że pomogłam ;)
Pozdrawiam.
3 5 3
  • Duox
  • Rozwiązujący
2010-03-30T17:59:41+02:00
A) 3(3-x)+2x=8-2(x-1)
9-3x + 2x =8 - 2x -2
9 -5 x = 8 - 2x -2
9 -8 + 2 = -2x + 5x
3 = 3 x | podzielone przez 3
1 = x
b) 4x+5-(3x+6)=2(2+x)-4
4x -15x -30 = 4 + 2x -4
11x -30 = 4 + 2 x - 4
11x - 2 x = 4 -4 + 30
9 x =30 | podzielone przez 9
1 x = 3 i 1/3 (jedna trzecia)
c) 4-5(3-x)=-x-(3-2x)
4-15 -5x = 3x - 2x²
-11 - 5x = 3x -2x²
-11 = -2x -2x² | podzielone przez 2 x
-5,5 x = x
-4,5 = x
Równanie jest sprzeczne
d) x-(7+2x)=2(x-1)+1
-7x -2x² = 2x - 2 + 1
-9 x - 2x² = -1 | podzielone przez x
-9 - 2x = -1 x
-9 = 3 x | podzielone prze 3
-3 = x
2 1 2
2010-03-30T18:00:18+02:00
A)
3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
-3x+2x+2x=8+2-9
4x-3x=10-9
x=1

b)
4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
4x-3x-2x=4-4-5+6
4x-5x=10-9
-x=-1/*(-1)
x=1

c)
4-5(3-x)=-x-(3-2x)
4-15+5x=-x-3+2x
5x+x-2x=-3-4+15
6x-2x=15-7
4x=8/:(-4)
x=-2

d)
x-(7+2x)=2(x-1)+1
x-7-2x=2x-2+1
x-2x-2x=-2+1+7
x-4x=8-2
-3x=-6/:(-3)
x=2
3 3 3